2014
DOI: 10.1016/j.jcf.2013.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis and pregnancy in the modern era: A case control study

Abstract: Pregnancy does not lead to immediate or medium-term adverse effects for CF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 15 publications
(16 reference statements)
3
29
1
5
Order By: Relevance
“…The rare cases of maternal deaths that have been reported during pregnancy are consistent with the findings of this report, which used a much larger population [14,20,29]. Case-control studies of pregnant women with CF matched with non-pregnant CF women have found no difference in BMI or in respiratory function both intra-and post-partum [17,20,23,24]. These results suggest that, over the same time period, pregnant women with CF had the same respiratory and overall health parameters as non-pregnant CF women.…”
Section: Discussionsupporting
confidence: 88%
“…The rare cases of maternal deaths that have been reported during pregnancy are consistent with the findings of this report, which used a much larger population [14,20,29]. Case-control studies of pregnant women with CF matched with non-pregnant CF women have found no difference in BMI or in respiratory function both intra-and post-partum [17,20,23,24]. These results suggest that, over the same time period, pregnant women with CF had the same respiratory and overall health parameters as non-pregnant CF women.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results have been demonstrated in other recent studies, with women who became pregnant experiencing similar respiratory and health trends as those who did not, although in some reports their utilization of health resources was greater. [32][33][34] Whether or not pregnancy impacts on the trajectory of progression of lung disease for patients with CF, there are physical and emotional demands of child rearing that have the potential to reduce any individual parent's ability to adhere to maintenance therapies themselves. This may lead to a deterioration in their own health.…”
Section: Impact Of Cf On Maternal Outcomesmentioning
confidence: 99%
“…With more than half the CF patients in the U.S. now over the age of 18 years (3), conversations about family planning, contraception and pregnancy have become an everyday occurrence in adult CF clinics (46). There are some known complications of pregnancy in CF (5, 7), but generally, maternal outcomes are not significantly altered by pregnancy and childbirth (8, 9). However, little is known about the intersection of contraception and chronic CF medications on pregnancy and fetal and maternal outcomes.…”
Section: Introductionmentioning
confidence: 99%